The Paradox of Agile Systems: A Phenomenological Study of Innovation Implementation Challenges in Healthcare Operations - Sayudin Sayudin (Journal of Innovation and Operational System, 2025)
The healthcare sector faces increasing pressure to adopt agile methodologies to enhance operational efficiency and adaptability. However, the implementation of agile systems in healthcare often encounters significant challenges, creating a paradox where intended improvements lead to workflow disruptions and resistance. This phenomenological study explores the lived experiences of 20 healthcare professionals, including clinicians, administrators, and IT specialists, to identify key barriers to agile adoption. Using semi-structured interviews and thematic analysis, the research examines the misalignment between agile principles and healthcare’s structured, risk-averse environment. Findings reveal that workflow disruption (75% of participants), resistance to change (65%), and training gaps (55%) are the most critical challenges, exacerbated by insufficient leadership support (40%). The study highlights the need for contextual adaptation of agile frameworks, role-specific training, and stronger change management strategies to facilitate smoother implementation. Practical implications include recommendations for hybrid agile-waterfall models, revised performance metrics, and dedicated change-management teams to bridge gaps between clinicians and IT staff. The research contributes to both theory and practice by emphasizing human-centric approaches to agile transformation in healthcare, offering actionable insights for policymakers and healthcare leaders. Future research should explore longitudinal impacts of hybrid models and patient perspectives on agile-driven care delivery.